Surface Degradation Analysis of Vacuum Composite Epoxy Resin Insulation Material Using Coastal Sand and Filler Containning Much Calsium - Moh Toni Prasetyo (Universitas Muhammadiyah Semarang, 2016)
Abstract. One of the insulating polymer in high voltage air insulation materials is epoxy resin because it has severaladvantages. However, has a degradation of the surface due to environmental pollution. Material that was used in this research was epoxy resin polymer isolation using of comparison values, material DGEBA : MPDA were 1:1, with the increase filler. Vacuum method to left out void. Research was done in laboratory according to standard IEC 587: 1984. High voltage electrodes were connected to high voltage AC generator 3.5 KV. The ground electrode was connected to oscilloscope for measuring the leakage current. The effect of variation were analyzed. From the results of the research, the composite are categorized as hydrophobic and partially wetted. The increase concentration of filler caused the increase in contact angle, slow down the aging on the surface of insulating material. Concentration value of filler that had the optimal performance was 40%.